Preliminary research: Identification of Difficulty in Chemical Learning Based On Teacher and Student Perspectives - Risvayani, Risvayani; Permanasari, A; Musthafa, I (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2023)
The purpose of education is to create a society which has the scientific literacy skills. So that goal is reached it is necessary teach and develop competencies that support skills. This study is a preliminary study in the identification of the problems perspectives by teachers and high school students in learning chemistry. The method used in this study is a survey method using a questionnaire. Respondents consisted of 10 teachers and 22 students senior high school in Bandung. From the results of the survey the problems perspectives by the students, interest and motivation in learning chemistry students is still low. It can be seen from the student questionnaire (question 1,2,3, and 4). In addition to low literacy student chemistry can be concluded from the results of the questionnaire related to the learning habits of students in applying chemistry in everyday life, 59, 1% sometimes, 27.3% often, 9.1% and 4.5% always never. From the survey results the authors focus on three main issues in teaching chemistry ie, level of difficulty of the material, the selection of teaching and learning context model of chemistry in everyday life is not always delivered on the learning process. Teacher as a key component in education need to be equipped with a good understanding and skills to implement learning that can develop chemistry student literacy. Knowledge is always evolving as the development time, teachers are required to continually update the scientific study. Difficulties experienced teachers is the failure to trigger the birth of learning in students and led to the view that chemistry is a difficult lesson. Based on the results of the survey above, learning will be more meaningful if using social-scientific issues that are relevant to the material being taught in order to achieve educational goals.